2022
DOI: 10.3390/land11010080
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Urbanization to Improve Agriculture Water Use Efficiency—An Empirical Analysis Based on Spatial Perspective of Panel Data of 30 Provinces of China

Abstract: China has witnessed accelerated urbanization since the reforms and open policies which began in 1978. This eventually resulted in increased residential water requirements and worsening water shortages, particularly in the current century. In the context of resource and environmental constraints, improving agricultural water use efficiency (AWUE) is a crucial issue to ensure food security, improve the ecological environment, and meet the needs of sustainable agricultural development. Based on the panel data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…In contrast, DEA is a non-parametric approach used to measure the efficiency of decisionmaking units (DMUs) of the same type, according to multiple inputs and multiple outputs. It uses a linear programming mathematical approach to evaluate the relative efficiency of the DMUs [23,24], and it can also reduce the subjective influence of ring-index weighting through automatic weighting, and it can clearly show the combinations of multiple inputs and multiple outputs [25]. However, the traditional DEA method has difficulty in comparing and evaluating multiple effective decision-making units, and it cannot explain cases where the efficiency value is greater than 1.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, DEA is a non-parametric approach used to measure the efficiency of decisionmaking units (DMUs) of the same type, according to multiple inputs and multiple outputs. It uses a linear programming mathematical approach to evaluate the relative efficiency of the DMUs [23,24], and it can also reduce the subjective influence of ring-index weighting through automatic weighting, and it can clearly show the combinations of multiple inputs and multiple outputs [25]. However, the traditional DEA method has difficulty in comparing and evaluating multiple effective decision-making units, and it cannot explain cases where the efficiency value is greater than 1.…”
Section: Introductionmentioning
confidence: 99%
“…The findings exhibit that GDP positively and significantly influences FPI and WPROD despite the break years considered. The outcomes of the research are analogous to the conclusions of (Lu et al, 2022;Zhou et al, 2022). The economic rationale underlying the positive impact of GDP growth lies in the increased investments and technological advancements within T A B L E 4 squares method.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the authors recommend that water production and its resources should be allocated towards higher productivity. (Lu et al, 2022) examined the factors of water productivity in provincial data and concluded that urbanization and income have a specific role in water and food productivity across provinces. The authors also claimed that sustainable growth in macro-economic factors reduces the influence of water misuse and low food production.…”
Section: The Role Of Gdp and Renewable Energy Consumptionmentioning
confidence: 99%
“…Based on the unique perspective of industry and enterprise, this paper discusses the effect of industrial structure upgrading and CSR on carbon emissions, and the regulatory effect of CSR. Additionally, existing research has shown that geospatial factors must be considered in economic management research [68][69][70]. Industrial development, enterprise behavior, and pollution emissions all have strong spatial attributes, but few studies have paid attention to that.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%